Exaction of the optic disk boundary in digital fundus images - REILLY, RICHARD (IEEE, 1999)
The methods of active contours (?snakes?) and level sets were applied to images of the retina in order to locate the outer boundary of the optic disk. A gradient-vector-flow based active contour was used as it performed well over a large range of initial conditions. Images were pre-processed to lessen the influence of blood vessels on boundary detection. Both active contours and level set methods accurately located the correct boundary; level set methods were computationally more intensive
PUBLISHED
Keywords: Administrative Staff Authors